Conebeam CT of the Head and Neck, Part 2: Clinical Applications - Miracle, A.C. (AJNR Am J Neuroradiol, 2009)
SUMMARY: Conebeam x-ray CT (CBCT) is being increasingly used for point-of-service head and neck and dentomaxillofacial imaging. This technique provides relatively high isotropic spatial resolution of osseous structures with a reduced radiation dose compared with conventional CT scans. In this second installment in a 2-part review, the clinical applications in the dentomaxillofacial and head and neck regions will be explored, with particular emphasis on diagnostic imaging of the sinuses, temporal bone, and craniofacial structures. Several controversies surrounding the emergence of CBCT technology will also be addressed.